An Empirical Analysis of Veterinary Certification, Perceived of Freshness and Price Suitability on Repurchase Intentions of Certified Beef in Pekanbaru - Ilham, Muhammad; Syahlani, Suci Paramitasari; Suryanto, Edi (Buletin Peternakan, 2025)
Rapid economic growth has led to an increase in the consumption of meat in the city of Pekanbaru in Riau Province, Indonesia. This calls greater attention from the government and animal product business units to improve the quality of meat supply. Implementing hygiene and sanitation practices along meat distribution channels is one strategy to enhance the quality of meat. The Indonesian government requires meat products to have certification in the form of a Veterinary Control Number (NKV). This study aims to study the effect of NKV certification marks, superior value of fresh beef, and perceived price suitability on the intention to repurchase NKV-certified beef. This study was conducted using a mixed method, using in-depht interview and survey design. The questionnaires were distributed through online and offline methods to a sample of 200 respondents, who were selected using judgemental sampling method based on the following criteria: (1) they were residents of the city of Pekanbaru; (2) they were at least 21 years old; (3) they had engaged in buying beef. The questionnaire consisted of 22 questions regarding NKV labelling, superior value of fresh beef, perceived price suitability, and intention to repurchase NKV-certified beef. Data were analysed with linear multiple regression analysis using SPSS 26 software package. The results of the t test showed that only the superior value of fresh beef had no significant influence (β = 0.075) on the intention to repurchase certified beef in Pekanbaru, while the NKV certification mark (β = 0.160) and perceived price suitability (β = 0.447) had a significant influence on the intention to repurchase certified beef. This study shows that the research model explains 28.4% of the variability in the intention to repurchase beef. This research concluded that the NKV certification mark and perceived price suitability are important factors that influence the intention to repurchase beef in Pekanbaru City.